Recurrent Episodes of Acute Pancreatitis as an Initial Presentation of Systemic Lupus Erythematosus and Autoimmune-Associated Hemophagocytic Syndrome - Siba Prasad Dalai; Pooja Uppu; Shrey Aradhye; Brijesh Raj Swain; Mrunmaya Ricky Jena; Chandan Das (Dr. Annil Mahajan, 2023)
Acute pancreatitis (AP) is a rare but fatal complication of systemic lupus erythematosus (SLE). A 40-year-old male presented with high-grade intermittent fever, abdominal pain & painless oral ulcers. Investigations revealed features suggestive of AP and coexistent SLE. Based on the H score and bone marrow aspiration findings, the diagnosis of secondary hemophagocytic syndrome (HPS)/autoimmune associated HPS (AAHS)/macrophage activation syndrome (MAS) was made. Autoimmune-associated HPS, we report a 40-year-old male case of SLE who presented with features suggesting AP, developed macrophage activation syndrome (MAS) on day 7 of admission.